اللطائف في بيان سبل الطوائف: المنعم عليهم، المغضوب عليهم، الضالين: دراسة تحليلية موضوعية - ابن طنطاوي، عرفة (عبدالفتاح محمود إدريس, 2022)
اللطائف في بيان سبل الطوائف"، هو عنوان دراسة بحثية قدمها الباحث وتناولها بأسلوب علمي سهل المأخذ قريب التناول، وقد بين فيها سبل المكلفين وانقسامهم إلى ثلاث طوائف وهم: (المنعم عليهم، المغضوب عليهم، الضالون)، فبين سبيل أهل السعادة ورغب فيه، وأهل السعادة هم: (المنعم عليهم) بسلوك الصراط المستقيم، وهم الذين جمعوا بين الإيمان والعلم والعمل، وبين سبل أهل الشقاوة وحذر منها ومن سلوك سبلها، وأهل الشقاوة هم: (المغضوب عليهم، والضالون) وهم ما بين: عالم (مغضوب عليه) لأنه لم يعمل بعلمه ولم ينتفع به ولم يرفع به رأسا كـــ "اليهود"، وما بين عابد (ضال) عبد الله على جهل فلم تنفعه عبادته ولم ينتفع بها ولم يرفع بها رأسا كــــ "النصارى". The politeness in explaining the ways of the sects” is the title of a research study presented by the researcher and dealt with in an easy-to understand scientific manner, in which he explained the ways of the taxpayers and their division into three sects: And the people of happiness are: (the one who has favored them) by walking the straight path, and they are the ones who combined faith, knowledge and action, and explained the paths of the people of misery and warned against them and against taking their paths. He did not act upon his knowledge, did not benefit from it, and did not raise his head with it, Like “the Jews”, and between a (misguided) worshiper he worshiped God in ignorance, his worship did not benefit him, he did not benefit from it, and he did not raise a head with it, like "Christians".
Keywords: أهل السعادة -- الصراط المستقيم -- أهل الشقاوة -- القرآن الكريم -- الشواهد القرآنية